The Corelation Of Workshop Facilities To The Academic Achievement Of Eleventh Students Welding Engineering In Smaw Subjects Of SMK Negeri 1 Sumatera Barat - Reza Ramadhan Prabulingga; Hendri Nurdin; Waskito Waskito; Irzal Irzal (Jurnal Vokasi Mekanika (VoMek), 2025)
The quality of school education is driven by several factors. These factors encompass school-related elements, pedagogical approaches, learning processes, environmental influences, learning facilities, and the allocation of learning time. It is evident that facilities and infrastructure represent a significant factor in the achievement of students. At SMK Negeri 1 West Sumatra, the Shielded Metal Arc Welding technique subject is used as the criterion for the completion of class 11 students. However, observations indicated that student academic outcomes were not ma11mized. This study explores the correlation between the availability of workshop infrastructure and the academic performance of Class 11 students enrolled in the SMAW (Shielded Metal Arc Welding) technique at SMK Negeri 1 West Sumatra. The investigation employs a correlational method to analyse the data. This study's population comprises 25 students enrolled in the 11th grade Welding Engineering programme, who utilise the Total Sampling Technique. The findings of the product moment correlation analysis demonstrate that the calculated r value of 0.595 exceeds the r table value of 0.396. It is evident that, with a statistical significance at p = 0.001, lower than 0.05, the alternative hypothesis (Ha) is confirmed. Considering the study’s findings, the alternative hypothesis (Ha) is accepted, signifying a robust correlation between workshop facilities and learning achievement. The findings of the analysis yielded a coefficient of determination of 35.4%, indicating that the impact of workshop facilities on student learning achievement is 35.4%. Conversely, a residual of 64.6% is attributed to external factors that were not considered in the study.